Resource Significant Cost and Time Models for Building Projects - Nabil Dmaidi (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Cost and time models have been developed for road and bridge projects using resource significance analysis, which is in turn based on the 80/20 rule. The work packages in these models are designed to relate to site operations. They serve as the basis for measurement, estimating, planning, valuation and control in civil engineering projects. For defined categories of work, a standard set of work packages have been developed which consistently contribute about 90% of a project's resource costs and hours. The resource significant cost and time models for bridges and roads predict cost to an accuracy of 4% Cv and 3% Cv respectively. The resource hours for a project can be predicted to an accuracy of 6% Cv for bridges and 3% Cv for roads. The bridge model contains 26 work packages and the road model contains 22 work packages. Coarser models have also been developed for situations where the road or bridge is only part of an overall project, with only a small loss of accuracy.